A gestão da cadeia de suprimentos das redes regionais de varejo de frutas, legumes e verduras no Rio Grande do Sul - Brandão, Janaína Balk (2011)
This thesis study aims to verify what conditions the adoption of governance structures in the formation and management of supplies chains in the networks of fruit and vegetables retail in the state of Rio Grande do Sul. For this, the main question for this research is: What are the motivations that take to the structures of governance adopted in the supply chains of retail organizations for FLV? The theorical framework used to help in the comprehension of the complex relationships established in the competitive modern environment is based, above, in the New Institucional Economy, in the Theory of Transaction Costs in the approach of Management in Chain of Supplies and in the Competitive Strategies of network organizations. As a level of analysis the chain of supplies of the retail companies is adopted, from the perspective of internal chain until the interorganizational arrangements. The methodological option performed for this investigation is the Case Study, considering that three regional networks of retail and six suppliers were analysed, covering the area of 5 mesoregions of the state. The choice of the cut on what refers to the section of fruits and vegetables is related to the specificities specially challenging on the distribution of the department of perishable foods and the growing search for health through the ingestion of more healthy , functional and with good nutritional aspects foods. This conjuncture has reflected on the raising of demand of these products and in the reorganization of all productive chain, reaching, specially, the initial link considered in this study: the farmers. As results it is verified that the retail networks when performing the management of their supplying chains use hibrid structures of governance with differente levels of coordination, considering the attributes of the transactions. But, also, conditioned by the characteristics imposed by the generic strategy adopted in each network as a way to answer their consumers. From the sight ocf impact on structuring the chains of supplies for the farmers it is seen that as the demand of the consumers gets higher, proportionally the need of coordinating the chain is increased, forcing the development of specific investments, increasing the mutual dependence. This takes the retail to adopt a more collaborative behavior in the chain.